2020
DOI: 10.1109/access.2020.3007771
|View full text |Cite
|
Sign up to set email alerts
|

A New Strong Adversary Model for RFID Authentication Protocols

Abstract: The paper was created with using institutional support for long-term conceptual development of research organization University of Finance and Administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…2) We present an off-line password guessing by an insider attacker against the proposed protocol by Yu et al [22], IoV-SMAP. We also show that the protocol could be compromised under the Hosseinzadeh et al [24] adversarial model. 3) We show that it is possible to extend the Safkhani et al's attack on GUMAP family of protocols [20] to EGP also.…”
Section: A Our Contributionsmentioning
confidence: 79%
See 2 more Smart Citations
“…2) We present an off-line password guessing by an insider attacker against the proposed protocol by Yu et al [22], IoV-SMAP. We also show that the protocol could be compromised under the Hosseinzadeh et al [24] adversarial model. 3) We show that it is possible to extend the Safkhani et al's attack on GUMAP family of protocols [20] to EGP also.…”
Section: A Our Contributionsmentioning
confidence: 79%
“…K V S is known to any vehicle or IS. Hence, following the adversarial model which has been proposed by Hosseinzadeh et al [24], compromising any vehicle compromises whole the network. The inverse of the binary value b (X )i…”
Section: ) Common Master Keymentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, Wang and Ma [34] proposed two RFID authentication protocols, a server-less one and a server-mounted one. But later analyses [35], [36] showed that the server-less version cannot resist traceability attacks, and the server-mounted version suffers from impersonation attacks. In 2015, Srivastava et al [37] proposed an authentication protocol to protect TIMSs, which is based on hash function and shared secrets.…”
Section: Related Workmentioning
confidence: 99%
“…This article shows that Safkhani et al's protocol [20] is lack of forward secrecy and scalability. In 2020, Hosseinzadeh et al [36] introduced an amended version of Wang and Ma's server-mounted protocol [34], addressing its security flaws.…”
Section: Related Workmentioning
confidence: 99%